Erratum: Allergic rhinitis: Review of the diagnosis and management: South African Allergic Rhinitis Working Group - Guy A. Richards; Marinda McDonald; Claudia L. Gray; Pieter De Waal; Ray Friedman; Maurice Hockman; Sarah J. Karabus; Cornelia M. Lodder; Tshegofatso Mabelane; Sylvia M. Mosito; Ashen Nanan; Jonny G. Peter; et al. (South African Family Practice)
No abstract available.